Pengaruh Kompensasi Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada MPS KUD Tani Bahagia - Nafakhati Salma Nuha; Mohammad Khusnu Milad (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to analyze the influence of compensation and work motivation on employee performance at MPS KUD Tani Bahagia Mojokerto. The research employed a quantitative approach with a population of 47 employees and a sample of 32 respondents selected through a cluster random sampling technique. Data were collected using a five-point Likert scale questionnaire and analyzed through validity tests, reliability tests, multiple linear regression, F-test, and t-test using SPSS 25. The results show that compensation has a positive and significant effect on employee performance (sig. 0.000 < 0.05; coefficient 0.722), while work motivation also has a positive and significant effect (sig. 0.000 < 0.05; coefficient 0.418). Simultaneously, compensation and work motivation significantly affect employee performance (F = 62.669; sig. 0.000 < 0.05). The R Square value of 0.812 indicates that 81.2% of employee performance variation is influenced by these variables, while 18.8% is explained by other factors. The findings highlight that fair compensation and high work motivation significantly contribute to improved employee performance.